1997
DOI: 10.1520/jfs14146j
|View full text |Cite
|
Sign up to set email alerts
|

PCR-Based DNA Typing of Saliva Stains Recovered from Human Skin

Abstract: Human bites in cases of homicide, sexual assault, and abuse are often distorted due to the elasticity and curvature of the skin. Physical comparison of a bite mark to a suspect's teeth is sometimes difficult. Saliva, which is usually deposited during biting, can be collected and analyzed to identify the perpetrator. Using simulated bite mark situations in two experimental series, three samples of 40 μL of whole saliva were deposited on the skin of 27 cadavers (at 33 sites) and three samples of 100 μL of whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 25 publications
1
38
0
1
Order By: Relevance
“…The biological basis of bite-mark analysis has centred on the recovery of salivary DNA and much of this work has been pioneered by Sweet who investigated the deposition of saliva during the biting process and its collection over protracted periods of time from cadavers [48,49]. In order to maximize the DNA collected, Sweet recommends that bite-marks should be 'double swabbed' , the first swab being moistened with distilled water and the second being dry.…”
Section: Biological Techniques For Bite-mark Comparisonmentioning
confidence: 99%
“…The biological basis of bite-mark analysis has centred on the recovery of salivary DNA and much of this work has been pioneered by Sweet who investigated the deposition of saliva during the biting process and its collection over protracted periods of time from cadavers [48,49]. In order to maximize the DNA collected, Sweet recommends that bite-marks should be 'double swabbed' , the first swab being moistened with distilled water and the second being dry.…”
Section: Biological Techniques For Bite-mark Comparisonmentioning
confidence: 99%
“…Bite marks on human flesh have a very limited duration of recognition before distortion sets in, requiring immediate identification, comparison and matching with the dentition of the alleged perpetrator [8]. However, the deposition of saliva into the tooth indentations might allow recovery of salivary cells to permit DNA identification of the retained genetic material that may match that of the potential perpetrator [9].…”
Section: Bite Marksmentioning
confidence: 99%
“…Studies conducted under controlled laboratory conditions have indicated that the DNA analysis of saliva placed on the skin of volunteers or cadavers may help in the identification of individuals (Sweet et al, 1997a;Anzai-Kanto et al, 2005;Kenna et al, 2011). However, the application of this approach to an actual criminal case has been reported only once before in forensic literature.…”
Section: Introductionmentioning
confidence: 99%